Prenatal Household Air Pollution Exposure, Cord Blood Mononuclear Cell Telomere Length and Age Four Blood Pressure: Evidence from a Ghanaian Pregnancy Cohort - Kaali, Seyram (Toxics, 2021)
Associations between prenatal household air pollution exposure (HAP), newborn telomere length and early childhood blood pressure are unknown. Methods: Pregnant women were randomized to liquefied petroleum gas (LPG) stove, improved biomass stove or control (traditional, open fire cook stove). HAP was measured by personal carbon monoxide (CO) (n = 97) and fine particulate matter (PM(2.5)) (n = 60). At birth, cord blood mononuclear cells (CBMCs) were collected for telomere length (TL) analyses. At child age four years, we measured resting blood pressure (BP) (n = 97). We employed multivariable linear regression to determine associations between prenatal HAP and cookstove arm and assessed CBMC relative to TL separately. We then examined associations between CBMC TL and resting BP. Results: Higher prenatal PM(2.5) exposure was associated with reduced TL (β = −4.9% (95% CI −8.6, −0.4), p = 0.03, per 10 ug/m(3) increase in PM(2.5)). Infants born to mothers randomized to the LPG cookstove had longer TL (β = 55.3% (95% CI 16.2, 109.6), p < 0.01)) compared with control. In all children, shorter TL was associated with higher systolic BP (SBP) (β = 0.35 mmHg (95% CI 0.001, 0.71), p = 0.05, per 10% decrease in TL). Increased prenatal HAP exposure is associated with shorter TL at birth. Shorter TL at birth is associated with higher age four BP, suggesting that TL at birth may be a biomarker of HAP-associated disease risk.